Clinical impact of single nucleotide polymorphisms within interferon signaling pathway gene in pregnant women with COVID-19 - Türkseven, Burcu; Demir, Nazlım A; Sümer, Şua; Ural, Onur; Özdemir, Ebru M; Seçilmiş, Özlem; Çora, Tülin; Kıratlı, Hatice Esranur (The Journal of Infection in Developing Countries, 2025)
Introduction: This study aimed to investigate if gene expression modifications due to two different single nucleotide polymorphism (SNP) mutations within the interferon-α/β receptor-2 (IFNAR2) gene had an effect on clinical prognosis in pregnant coronavirus disease 2019 (COVID-19) patients. Methodology: The study included 173 pregnant patients who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) using real-time polymerase chain reaction (RT-PCR). Oligonucleotides were designed for the SNPs with nucleotide database codes rs13050728 and rs2236757 in the hospital’s genetic laboratory, and RT-PCR analyses were performed. Results: There was a significant difference in upper respiratory tract infection (URTI) symptoms (runny nose, nasal congestion, and fatigue); between rs2236757 normal–carrier–homozygous mutant pregnant women and the occurrence of symptoms (p = 0.004). However, these URTI symptoms were never seen in homozygous mutant pregnant women. Upon analysis of the relationship between rs13050728 normal–carrier–homozygous mutant pregnant women and the occurrence of symptoms, there was a significant difference between URTI symptoms, and nausea and vomiting (p = 0.001, p = 0.027, respectively). The URTI symptoms were never seen in homozygous mutant and carrier pregnant women. There was no significant association between rs13050728 and rs2236757 normal–carrier–homozygous mutant pregnant women and severity of disease, intensive care unit admission, pregnancy complications, need for oxygen support, and radiologic involvement. Conclusions: The results of this study will serve as a guide in identifying high-risk individuals, providing treatment, and contributing to the understanding of genetic factors in future viral pandemics.